The Instrumental Enrichment Program [PEI] as a Pedagogical Proposal for the Risks of Exposure in Pesticide Applicators - Azucena Benítez Medina,; Ruvalcaba Ledezma Jesús Carlos,; Jeiry Toribio Jiménez,; Claudia Isabel Martínez Alcalá,; Beltrán Rodríguez María Guadalupe,; Reynoso Vázquez Josefina,; Aldo Pelcastre Neri,; Olga Rocío Flores Chávez,; Alfonso Reyes Garnica, (Public Health, 2026)
Pesticide applicators are unaware of the risks to which they are exposed because they do not have specialized equipment to avoid exposure to them, the regulation of pesticides includes shortcomings from environmental legislation, since currently banned agrochemicals are used in Europe and the United States. United since 2007. Objective. Establish as a pedagogical proposal the Instrumental Enrichment Program for pesticide applicators from a qualitative perspective. Material and methods. A systematic review was made on the internet, based on articles indexed in Crossref using keywords such as poisoning, and Instrumental Enrichment Program. Results. The IEP has significant positive effects on reasoning skills in socially and culturally disadvantaged children through brain plasticity. In type II diabetes education in the community of Tenango de Doria, Hidalgo, the study demonstrated a decrease in serum glucose and glycosylated hemoglobin, after the intervention and in 62 primary school children, a 4.8% reduction in obesity. In summary, of a total of 29 references reviewed, 15% belong to postgraduate thesis, national and international official pages, they deal with the definition of pesticide poisoning and its standardization, 85% of references are to reference articles related to pesticide poisoning and the Instrumental Enrichment program. Conclusions Based on the revised references, the Instrumental Enrichment Program represents an innovative opportunity to work with pesticide applicators with the vision to evoke learning to reduce or avoid exposure to them.